European public health best practice portal - process and criteria for best practice assessment - Magdalena Stepien; Ingrid Keller; Marianne Takki; Sandra Caldeira (BMC, 2022)
Abstract Background Non-communicable diseases (NCDs) are major and growing burden on population health and the use and cost of healthcare in EU Member States and beyond. Different countries face many common challenges in public health and can learn from each other. The exchange of 'best practices' is one way to tackle the observed disparities in health sector. To address the United Nations Sustainable Development Goals, the European Commission developed the EU Public Health Best Practice Portal to facilitate the exchange of best practices and facilitate their implementation in other EU countries or regions. The ultimate aim of the portal is to reduce NCDs burden and the prevalence of their risk factors by promoting implementation and scale up of evidence-based effective interventions in the areas of health promotion, disease prevention and management of NCDs. Results This article presents the rationale and the process, ranging from best practice assessment to their transfer to interested Member States, applied in the EU Public Health Best Practice Portal. The portal selects best practices using rigorously defined criteria for best practice assessment. This article further provides an overview of other similar initiatives in Europe and internationally that collect and disseminate information on interventions and actions to combat NCDs. Conclusion Exchange of best practices is a promising tool in tackling NCDs. Transfer and scaling up of policies and interventions between countries may contribute to tackle disparities observed between countries in regards to the prevalence of risk factors and associated diseases.